Characterization symptomatology and molecular from papaya ringspot (PRSV) that infects Carica papaya L. in northern Peru - Valderrama, Shirley (2015)
The objective of present study was symptomatic and molecular characterization of the virus that infects Carica papaya L. in areas of northern Peru. To do this, of different fields were collected leaves of C. papaya with mosaic symptoms, chlorosis and distortion the leaf. Sap of these leaves was inoculated mechanically onto virus-free plants of C. papaya, Chenopodium murale, Ch. amaranticolor, Ch. quinoa, Cucumis melo, C. sativus and Cucurbita pepo; which they were kept at room temperature for 45 days, after which young leaves in of C. papaya, mosaic, distortion and reduction of the leaf blade was observed; in the species C. melo, C. sativus and Cucurbita pepo systemic chlorosis. Ch. murale, Ch. amaranticolor and Ch. quinoa they no showed symptoms evident. The plants infected were analyzed by serological technique NCM-ELISA and RT-PCR proving that the virus that is infecting the plantations assessed in the north of Peru, it is the papaya ringspot virus (RSVP).